Developmental validation of the DNAscan™ Rapid DNA Analysis™ instrument and expert system for reference sample processing. (November 2016) - Della Manna, Angelo; Nye, Jeffrey V.; Carney, Christopher; Hammons, Jennifer S.; Mann, Michael; Al Shamali, Farida; Vallone, Peter M.; Romsos, Erica L.; Marne, Beth Ann; Tan, Eugene; Turingan, Rosemary S.; Hogan, Catherine; et al.
Highlights: Developmental validation of DNAscan/ANDE Rapid DNA Analysis System. The DNAscan System includes fully integrated Expert System software. Demonstrated concordance rate for allele calling is over 99.99%. The DNAscan System is suitable for use for forensic reference samples. Abstract: Since the implementation of forensic DNA typing in labs more than 20 years ago, the analysis procedures and data interpretation have always been conducted in a laboratory by highly trained and qualified scientific personnel. Rapid DNA technology has the potential to expand testing capabilities within forensic laboratories and to allow forensic STR analysis to be performed outside the physical boundaries of the traditional laboratory. The developmental validation of the DNAscan/ANDE Rapid DNA Analysis System was completed using a BioChipSet™ Cassette consumable designed for high DNA content samples, such as single source buccal swabs. A total of eight laboratories participated in the testing which totaled over 2300 swabs, and included nearly 1400 unique individuals. The goal of this extensive study was to obtain, document, analyze, and assess DNAscan and its internal Expert System to reliably genotype reference samples in a manner compliant with the FBI's Quality Assurance Standards (QAS) and the NDIS Operational Procedures. The DNAscan System provided high quality, concordant results for reference buccal swabs, including automated data analysis with an integrated Expert System. Seven external laboratories and NetBio, the developer of the technology, participated in the validation testing demonstrating the reproducibility and reliability of the system and its successful use in a variety of settings by numerous operators. The DNAscan System demonstrated limited cross reactivity with other species, was resilient in the presence of numerous inhibitors, and provided reproducible results for both buccal and purified DNA samples with sensitivity at a level appropriate for buccal swabs. The precision and resolution of the system met industry standards for detection of micro-variants and displayed single base resolution. PCR-based studies provided confidence that the system was robust and that the amplification reaction had been optimized to provide high quality results. The DNAscan integrated Expert System was examined as part of the Developmental Validation and successfully interpreted the over 2000 samples tested with over 99.998% concordant alleles. The system appropriately flagged samples for human review and failed both mixed samples and samples with insufficient genetic information. These results demonstrated the integrated Expert System makes correct allele calls without human intervention.